Social, Emotional, and Academic Impact of Residual Speech Errors in School-Aged Children: A Survey Study - Hitchcock, Elaine R.; Harel, Daphna; Byun, Tara McAllister (Seminars in Speech and Language, 2015)
Children with residual speech errors face an increased risk of social, emotional, and/or academic challenges relative to their peers with typical speech. Previous research has shown that the effects of speech sound disorder may persist into adulthood and span multiple domains of activity limitations and/or participation restrictions, as defined by the World Health Organization's International Classification of Functioning, Disability and Health model. However, the nature and extent of these influences varies widely across children. This study aimed to expand the evidence base on the social, emotional, and academic impact of residual speech errors by collecting survey data from parents of children receiving treatment for /r/ misarticulation. By examining the relationship between an overall measure of impact (weighted summed score) and responses to 11 survey items, the present study offers preliminary suggestions for factors that could be considered when making decisions pertaining to treatment allocation in this population.
Keywords: Residual speech errors; rhotic sounds; survey; socioemotional challenges